Longitudinal Evaluation of Transition Services ("LETS Study"): Protocol for outcome evaluation - Tsybina Irina; Kingsnorth Shauna; Maxwell Joanne; Bayley Mark; Lindsay Sally; McKeever Patricia; Colantonio Angela; Hamdani Yani; Healy Helen; Macarthur Colin (BMC, 2012)
Abstract Background Because of advances in medical treatment, most children with physical disabilities can expect to achieve near normal life spans. Typically, coordinated teams of health care providers in specialized pediatric settings care for these children. As these children reach adulthood, however, the availability of services and expertise changes because the adult health care system has different processes designed to meet their specialized needs. Gaps in continuity of care during the transition from pediatric to adult services, and associated poor health outcomes are well documented. In response, new models of care are being introduced to address the complex process of health care transition. This paper describes a study protocol of a client-centred, prospective, longitudinal, mixed-method evaluation of linked model of health care across the lifespan (the LIFEspan Model), offered by a pediatric rehabilitation centre and an adult rehabilitation centre. Method This project will include a process and an outcome evaluation of the LIFEspan Model. The process evaluation will detail the specific service delivery that occurs with respect to preparation for transition and transfer of care through chart audits of pediatric medical records and qualitative interviews with LIFEspan staff. The outcome evaluation will measure the effect of the model on: 1) maintaining continuity within the health care system from pediatric to adult care; and 2) secondary outcomes related to health, well-being, social participation, transition readiness, and health care utilization of youth with cerebral palsy and acquired brain injury. Standardized instruments will include Health Utilities Inventory, Assessment of Life Habits, Arc's Self-Determination, Assessment of Health-Related Quality of Life, Partners in Health Questionnaire, Social Support Questionnaire, and Self-Efficacy for Managing Chronic Disease. Discussion The LETS study will be original in its undertaking of a prospective examination of outcomes 1-year post-transition, use of multiple comparison groups, and absence of disability-related exclusion criteria ensuring that the transition experiences of varied populations of young people and their families will be represented. Trial registration http://www.clinicaltrials.gov, ID NCT00975338